FIRST STEP TOWARDS SMART CLASSROOM - IOT DEVICE FOR REGISTERING STUDENTS TO CLASSES - Sijan, Aleksandar; Ilic, Luka; Predic, Bratislav (Journal of process management and new technologies, 2023)
The use of IoT devices in the classroom has the potential to revolutionize the learning experience of students and professors. One such device is the NodeMCU, an open-source platform based on the ESP32 microcontroller. This paper presents device for registering students for classes and preparation for the experiment, which is conducted on our faculty where we work as teaching fellows, on the use of NodeMCU. In the first part of the paper, we will briefly look at some of the challenges in higher education in the Republic of Serbia and how we came up with the idea to improve the teaching process by creating a device for registering for classes. Next, we will explain in more detail the building elements of the device itself and how it works.